Gudeg dan Yogyakarta: Makanan tradisional sebagai instrumen diplomasi budaya indonesia - Nadhiroh, Elvinatun (Maliki Interdisciplinary Journal, 2025)
Gudeg is a traditional dish from Yogyakarta that holds significant cultural, historical, and social value. More than just cuisine, gudeg serves as a symbol of Javanese cultural identity and an integral part of local traditions. With the development of the concept of gastrodiplomacy, gudeg has emerged as a cultural diplomacy instrument for Indonesia, introducing the nation’s culinary richness and cultural values to the international stage. Packaging innovations, such as canned gudeg, have enabled its export and global recognition, expanding the reach of cultural diplomacy while supporting the creative economy and tourism sectors. Despite its great potential, the implementation of gastrodiplomacy through gudeg still faces challenges, including the lack of integrated promotion and intersectoral coordination. Therefore, a more collaborative and integrated strategy is needed among the government, culinary businesses, and tourism stakeholders. The effective use of information technology and digital promotion is also key to reaching a wider international audience. This study highlights the importance of preserving traditional culinary heritage while developing it as a strategic asset in cultural diplomacy and national development. With its unique taste and philosophy, gudeg stands not only as a culinary icon of Yogyakarta but also as a representation of Indonesia’s soft power in the era of globalization.